Dynamics of groundwater flow and upwelling pressure heads at a wetland zone in a headwater catchment - Waswa, George W.; Lorentz, Simon A. (Springer Nature, 2019)
The rate and direction of groundwater flow are a function of the gradient of the hydraulic head, whose components are gravity head and pressure head. This paper presents results and analyses of field observations of pressure head responses to some rainfall events of 2000/2001 summer season in a headwater catchment in South Africa. A transect spanning from a steep hillslope zone, through a transition zone and a flat low-lying wetland zone, to a stream channel zone was instrumented with tensiometers to monitor the responses of pore-water pressure to rainfall. The season’s late rainfall events simultaneously caused the pressurized pore-air driven Lisse effect water table response at the transition zone, and the capillary fringe-assisted groundwater ridging water table response at the wetland zone. During the events, the Lisse effect dissipated, but followed by sequences of stepped increases in pressure head in the deep soil profile at the transition zone. These stepped increases in pressure head, whose magnitudes increased with depth, were caused by the upwelling pressure heads induced by rainfall spike intensities at the wetland zone. These upwelling pressure heads could have major and disproportionate influence on the dynamics of groundwater flow.
Keywords: Capillary fringe; Groundwater ridging; Lisse effect; Upwelling pressure heads; Wetland zone